1995
DOI: 10.1080/09540129550126416
|View full text |Cite
|
Sign up to set email alerts
|

Group intervention to improve coping with AIDS-related bereavement: Model development and an illustrative clinical example

Abstract: Despite the widespread losses from AIDS, there have been no published evaluations of mental health interventions for people experiencing AIDS-related bereavement. We describe a cognitive behavioural coping model for support group interventions with people who experience an AIDS-related loss. The support group model consists of six primary components to address grief-related responses and the unique features of AIDS bereavement: social support and group cohesion; identification and expression of emotion; identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 0 publications
0
23
0
1
Order By: Relevance
“…Recent research demonstrated the efficacy of a bereavement support group intervention focused on stress and coping for HIV-positive and HIV-negative homosexual men (Goodkin et al, 1999). In prior research, we have found that a support and coping group intervention for persons experiencing AIDS-related bereavement based on these principles can produce reductions in grief reaction and psychological distress (Sikkema et al, 1995). Results of the present study suggest that interventions for coping with AIDS-related bereavement must also take into account therapeutic techniques and strategies used in the treatment of depression, anxiety and post traumatic stress disorder.…”
Section: Discussionmentioning
confidence: 94%
“…Recent research demonstrated the efficacy of a bereavement support group intervention focused on stress and coping for HIV-positive and HIV-negative homosexual men (Goodkin et al, 1999). In prior research, we have found that a support and coping group intervention for persons experiencing AIDS-related bereavement based on these principles can produce reductions in grief reaction and psychological distress (Sikkema et al, 1995). Results of the present study suggest that interventions for coping with AIDS-related bereavement must also take into account therapeutic techniques and strategies used in the treatment of depression, anxiety and post traumatic stress disorder.…”
Section: Discussionmentioning
confidence: 94%
“…Few intervention studies with HIV-infected individuals have focused specifically on bereavement. In a pilot study to the current research, Sikkema, Kalichman, Kelly, and Koob (1995) found that a group cognitive-behavioral coping intervention improved psychiatric functioning and reduced grief response in HIV-positive and HIV-negative participants. Also, Goodkin et al (1999) conducted a 10-session bereavement support group intervention with both HIVpositive and HIV-negative gay men who had recently lost a close friend or partner to AIDS.…”
mentioning
confidence: 87%
“…Goal setting (i.e., creating valued and attainable goals) is commonly used in behavioral health interventions (Strecher et al, 1995) and has been included in programs for people with serious physical illness such as HIV (e.g., Antoni, Ironson, & Schneiderman, 2007; Sikkema, Kalichman, Kelly, & Koob, 1995). Higher levels of positive affect and greater life satisfaction are found among people who perceive that they are making progress toward their goals (Brunstein, Schultheiss, & Grassmann, 1998; Carver & Scheier, 1990; Lent et al, 2005), and pursuing attainable goals (goals that are short-term and specific vs. distant and global) is associated with higher subjective well-being (Emmons, 1986, 1992).…”
Section: Intervention Developmentmentioning
confidence: 99%